No seasonal influence on cognitive performance in a national sample of older adults in New Zealand. (15th October 2019) - Barak, Yoram; Leitch, Sharon; Gale, Chris; Glue, Paul
Abstract: Objectives: A recent North American study reported seasonal differences in cognitive functioning in older adults. We assessed seasonality of cognitive functioning in a large data set of older adults in New Zealand. Methods: The International Residential Assessment Instrument‐Home Care (interRAI‐HC) data set was analysed using a non‐parametric method for testing seasonal distribution of cognitive and depression scale scores. Results: Participants were 73 285 New Zealanders 65 years and older who completed their first interRAI‐HC assessment (mean age, 81.4 years; 57% female). We analysed this sample cross‐tabulating season (summer, autumn, winter and spring) and the Cognitive Performance Scale (CPS) score (Kruskal‐Wallis test, P  = 0.45). Month‐by‐month CPS scores also demonstrated no variation (Spearman's test, P  = 0.96). There was no association between season of assessment and the Depression Rating Scale score, ruling out variability in affect impacting on cognitive performance (Kruskal‐Wallis test, P  = 0.99). Conclusion: Our findings, limited to the Southern Hemisphere, demonstrate a lack of seasonality in cognitive performance and impairment in older adults.